A Multifunctional Micellar Nanoplatform with pH‐Triggered Cell Penetration and Nuclear Targeting for Effective Cancer Therapy and Inhibition to Lung Metastasis. Issue 7 (15th January 2018) - Jing, Yuting; Xiong, Xiang; Ming, Yang; Zhao, Jingya; Guo, Xing; Yang, Guang; Zhou, Shaobing
Abstract: The enhancement of cellular internalization and subsequent achievement of a nuclear targeting of nanocarriers play an important role in maximizing the therapeutic potency and minimizing the side effects of encapsulated drugs. Herein, a multifunctional micellar nanoplatform simultaneously with high cell penetration and nuclear targeting through pH‐triggered surface charge reversal is presented. The miscellar system is constructed from poly(ethylene glycol)‐poly(ε‐caprolactone) with 2, 3‐dimethylmaleic anhydride‐Tat decoration (PECL/DA‐Tat). DA groups are used to mask the positive charge of Tat to prolong blood circulation of the nanocarriers. In the mildly acidic environment of tumor tissue, the system exhibits ultrasensitive negative to positive charge reversal, facilitating the cell internalization and subsequent nuclear targeting. The chemotherapeutic 10‐hydroxycamptothecin conjugated to methoxy polyethylene glycol, which is loaded in this micelle, obviously enhances cytotoxicity against tumor cells. The in vivo therapy in mice bearing 4T1 breast tumor reveals that the system has a significant enhancement of both the endocytosis and nuclear enrichment, showing a highly effective antitumor efficacy and inhibition to lung metastasis. Abstract : The high cell penetration and nuclear targeting with a multifunctional micellar nanoplatform are successfully realized both in vitro and in vivo through pH‐triggered surface charge reversal. The delivered anticancer drug with this nanoplatform displays a highly effective antitumor efficacy and an inhibition to the spontaneous lung metastasis.